Examining higher educational institutes for better growth of national economy through structured innovation. Issue 1 (2018) - Kashyap, Ankur; Agrawal, Rajat; Ghosh, P.K.
This study elucidates the role of structured innovation (SI) in the field of higher education and suggests the recommendations for its stakeholders. The process consists of comparing the reports available in public domain of some premier institutions on factors such as innovation factor, spin-off activities, programs running in higher educational institutes (HEIs) and assembling the entities like education and entrepreneurship linkage, commercialisation and fund seeking, intellectual property support to create a framework that would be relevant in present time. Soft system methodology (SSM) is used to implement these parameters in Indian HEIs. This study analyses the gaps between concerned areas of the real world system and conceptual system.